Functions of Oral Literature Malèlang Madiôn for Its Supporting Community in Aceh Barat Daya - Warnisa, Ifutya; Supriyanto, RM. Teguh; Nugroho, Yusro Edy (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
No study on functions of oral literature Malèlang Madiôn in Aceh Barat Daya has been conducted. Therefore, this study aims to seek novelty as a form of literature revitalization to avoid extinction. It proposes to describe the functions of oral literature Malèlang Madiôn for its supportive community in Aceh Barat Daya. The selected approach was folklore by using Bascom-Dundes' theories. Data were acquired from informants from Aceh Barat Daya through interviews and transcription, supported by a literature study. They were in the form of oral text Malèlang Madiôn. Analyses were carried out using the semiotic reading method through the following steps: (1) interviewing informants, (2) transcribing oral utterances into oral text, (3) reading oral text Malèlang Madiôn heuristically and hermeneutically, (4) revealing the functions of oral literature Malèlang Madiôn based on the function theory by Bascom-Dundes, (5) categorizing the functions of Malèlang Madiôn, and (6) describing the results and drawing a conclusion. The results point out several functions of oral literature Malèlang Madiôn for its supportive community, namely (1) as a projection system; (2) as a means of cultural institutions validation; (3) as an educational tool; (4) as a means of control and supervision for community norms; (5) as a means of social sanctions or punishment, and (6) as a means of social criticism.